Persepsi Santri tentang Moderasi Islam dan Wawasan Kebangsaan - Ratu Bai Rohimah (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2019)
This study aims to find out how the perceptions of santri at Tahfidzul Islamic Boarding School in Ar Rahmah's Qur'an on Islamic concepts and national insights, relationship between Islamic insight and insight into santri nationality, And what are the efforts to build Islamic insights and insights into the nationality of santri. Research in scientific papers uses quantitative descriptive analysis, with descriptive analysis method Quantitative. Can be obtained data that the students have a good understanding of Islamic concepts and nationalities, there is a significant relationship between the perceptions of santri about Islamic insights with national insight based on the Spearman Correlation Test of 0.578 and this shows a strong relationship between Islamic insights into the insights nationality.